Metabolism of Dendritic Cells in Tumor Microenvironment: For Immunotherapy - Peng, Xin; He, Youe; Huang, Jun; Tao, Yongguang; Liu, Shuang (Frontiers in Immunology, 2021)
Dendritic cells (DCs) are antigen-presenting cell which undertake a job on capturing antigens come from pathogens or tumors and presenting to T cells for immune response. The metabolism of DCs controls its development, polarization, and maturation processes, and provides energy support for its functions. However, the immune activity of DCs in tumor microenvironment (TME) is inhibited generally. Abnormal metabolism of tumor cells causes metabolic changes in TME, such as hyper-glycolysis, lactate and lipid accumulation, acidification, tryptophan deprivation, which limits the function of DCs and leading to the occurrence of tumor immune escape. Combined metabolic regulation with immunotherapy can strengthen the ability of antigen-presentation and T cells activation of DCs, improve the existing anti-tumor therapy, and overcome the defects of DCs-related therapies in current stage, which has great potential in oncology therapy. Therefore, we reviewed the glucose, lipid and amino acid metabolism of DCs, as well as the metabolic changes after being affected by TME. Together with the potential metabolic targets of DCs and possible antitumor therapeutic pathways were summarized.